Comparison of clinical cases of patients with exudative form of age-related macular degeneration after standard treatment and refusal of treatment - Dziuba, Alina (The Ukrainian Scientific Medical Youth Journal, 2025)
these clinical cases indicate high effectiveness of using anti-VEGF drug and positive dynamics in the treatment of exudative form of age-related macular degeneration according to standard protocols in patient Ch. and negative dynamics in patient T., who refused treatment. Examination of patients was carried out at the beginning of observation, after 12 and 24 weeks. Visual acuity was examined and optical coherence tomography was performed. In patient Ch. After three intravitreal injections of the anti-VEGF drug aflibercept (once every 4 weeks), visual acuity improved and signs of exudative age-related macular degeneration regressed as assessed by optical coherence tomography scans.